The analysis of the connection between plaque morphology of the asymptomatic carotid stenosis and ischemic brain lesions - Milošević Đorđe; Pasternak Janko; Popović Vladan; Nikolić Dragan; Milošević Pavle; Manojlović Vladimir (Vojnosanitetski Pregled)
Background/Aim. A certain percentage of patients with asymptomatic carotid stenosis have an unstable carotid plaque. For these patients it is possible to register by modern imaging methods the existence of lesions of the brain parenchyma - the silent brain infarction. These patients have a greater risk of ischemic stroke. The aim of this study was to analyze the connection between the morphology of atherosclerotic carotid plaque in patients with asymptomatic carotid stenosis and the manifestation of silent brain infarction, and to analyze the influence of risk factors for cardiovascular diseases on the occurrence of silent brain infarction and the morphology of carotid plaque. Methods. This retrospective study included patients who had been operated for high grade (> 70%) extracranial atherosclerotic carotid stenosis at the Clinic for Vascular and Transplantation Surgery of the Clinical Center of Vojvodina over a period of 5 years. The patients analyzed had no clinical manifestation of cerebrovascular insufficiency of the carotid artery territory up to the time of operation. The classification of carotid plaque morphology was carried out according to the Gray-Weale classification, after which all the types were subcategorized into two groups: stable and unstable. Brain lesions were verified using preoperative imaging of the brain parenchyma by magnetic resonance. We analyzed ipsilateral lesions of the size > or = 3 mm. Results. Out of a 201 patients 78% had stable plaque and 22% unstable one. Unstable plaque was prevalent in the male patients (male/female ratio = 24.8% : 17.8%), but without a statistically significant difference (p > 0.05). The risk factors (hypertension, nicotinism, hyperlipoproteinemia, and diabetes mellitus) showed no statistically significant impact on carotid plaque morphology and the occurrence of silent brain infarction. Silent brain infarction was detected in 30.8% of the patients. Unstable carotid plaque was found in a larger percentage of patients with silent brain infarction (36.4% : 29.3%) but without a significant statistical difference (p > 0.05). Conclusions. Even though silent brain infarction is more frequent in patients with unstable plaque of carotid bifurication, the difference is of no statistical significance. The effects of the number and type of risk factors bear no statistical significance on the incidence of morphological asymptomatic carotid plaque.